2004
DOI: 10.1136/ip.2003.002923
|View full text |Cite
|
Sign up to set email alerts
|

Are older drivers actually at higher risk of involvement in collisions resulting in deaths or non-fatal injuries among their passengers and other road users?

Abstract: Objectives: With more older drivers on the road, public concern has been expressed about their impact on traffic safety. This study revisited the question of driver age in relation to the risks of older drivers and others sharing the road with them, including pedestrians, passengers in the same vehicle, and occupants of other vehicles. Methods: Using United States federal data on fatal and non-fatal crashes, injury rates per driver were calculated for different types of road users. In addition, using data supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(84 citation statements)
references
References 18 publications
3
77
1
1
Order By: Relevance
“…Functional declines associated with medical conditions, rather than age alone, have been attributed to higher crash rates (Dobbs, 2008). Relative to younger drivers, older drivers tend to cause more multi-vehicle crashes and, because they are frailer, the severity of their injuries and fatality rates are disproportionately high (Bédard et al, 2002;Braver and Trempel, 2004;Cook et al, 2000;Evans, 2001;Li et al, 2003;Lyman et al, 2002). Unfortunately, evidence suggests that awareness of impairments does not necessarily result in appropriate or sufficient self-regulation of driving habits (Baldock et al, 2006;Banister and Bowling, 2004), necessitating in other interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Functional declines associated with medical conditions, rather than age alone, have been attributed to higher crash rates (Dobbs, 2008). Relative to younger drivers, older drivers tend to cause more multi-vehicle crashes and, because they are frailer, the severity of their injuries and fatality rates are disproportionately high (Bédard et al, 2002;Braver and Trempel, 2004;Cook et al, 2000;Evans, 2001;Li et al, 2003;Lyman et al, 2002). Unfortunately, evidence suggests that awareness of impairments does not necessarily result in appropriate or sufficient self-regulation of driving habits (Baldock et al, 2006;Banister and Bowling, 2004), necessitating in other interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Gustafsson et al (2015) showed that both age and gender affect the risk of PMI following car crashes. However, the correlation of older age and impairment risk was not as clear as has been found for fatality risk in a car crash (Augenstein et al 2005;Bédard et al 2002;Braver and Trempel 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Older drivers, on the other hand, are experienced and less likely to engage in unsafe driving behaviours (National Highway Traffic Safety Administration). Surprisingly, older drivers have one of the highest rates of collision per mile driven (Braver and Trempel, 2004;Daigneault et al, 2002b;Di Stefano and Macdonald, 2003). One explanation for increased collision risk in this age group is a characterized low mileage bias (Gallo et al, 1999;Kostyniuk et al, 2000).…”
Section: Introductionmentioning
confidence: 99%